Digestibility of Dry and Organic Matter of Oil Palm Leaves through Fermentation using different levels of Alfalfa Microbacteria-11 - Harnadi, Harnadi; Sukaryani, Sri; Purwati, Catur Suci (Jambura Journal of Animal Science, 2024)
This research aims to determine the effect of nutrient content in palm leaf fermentation using MA-11 on the value of Dry Matter Digestibility and Organic Matter Digestibility. This study used a completely randomized design (CRD) with a one-way pattern with four treatments and each treatment was repeated three times. P0: 250 grams of palm leaves + 0 ml dose of MA-11, P1: 250 grams of palm leaves + 2 ml dose of MA-11, P2: 250 grams of palm leaves + 4 ml dose of Ma-11, P3: 250 grams of palm leaves + 6 ml dose of Ma-11. The results of the study showed that the average value of Dry Matter Digestibility was obtained P0: 22.70%, P1: 24.95%, P2: 27.81% and P3: 45.64%, the average value of Organic Matter Digestibility was obtained P0: 17.68%, P1: 23.51%, P2: 25.78% and P3: 44.58%. The conclusion of this study is that palm leaf fermentation using a dose of 0 ml to 6 ml with a fermentation period of 9 days has a very significant effect on increasing the value of Dry Matter Digestibility and the value of Organic Matter Digestibility.